Sustaining business competitiveness : Merging eTIQa Insurance and Takaful. - Abdul Aziz Ibrahim (2015)
This case study is prepared as a situational analysis and consists of an introductory chapter, the definition of the merger itself and the motive for merger, situational analysis og the identified issues and recognized problems and will be prepare some solutions and recommendation in discussion forms and implementation. in the introductory chapter will explain the definition, its rational, motives and objectives of the merger, in connection to the people related dimension at Etiqa Kota Bharu Branch.